Prediction of psychological distress based on coronavirus anxiety and self-care among Iranian adolescents during the coronavirus epidemic - Sheikhi, Samira; Beikzadeh Oskoei, Azizeh; Ghayourvahdat, Bahman; Nasirian, Amir-Hossein (Chronic Diseases Journal, 2022)
BACKGROUND: The coronavirus disease-2019 (COVID-19) disease had a negative impact on adolescents’ physical and psychological health. This study aimed to investigate the association between coronavirus anxiety and self-care with psychological distress among Iranian adolescents during the coronavirus epidemic. METHODS: This was a descriptive-correlational study conducted on 419 Iranian adolescents in March 2021, in which the convenience method was adopted for sampling. An anonymous self-administered questionnaire was used, which included Corona Disease Anxiety Scale (CDAS), Corona Self-Care Questionnaire (CSCQ), and Kessler Psychological Distress Scale (K10). The data were analyzed using the SPSS software and also Pearson correlation coefficient and stepwise regression tests. RESULTS: The results showed that there was a significant relationship between coronavirus anxiety (r = 0.279, P < 0.001) and self-care (r = -0.265, P < 0.001) with self-care. The results also indicated that coronavirus anxiety and self-care could predict approximately 17% of the variance in psychological distress (R2 = 0.168; F = 13.55; P < 0.001). CONCLUSION: Due to the role of coronavirus anxiety and self-care in predicting the psychological distress among Iranian adolescents during the coronavirus epidemic, it is suggested to design interventions to improve psychological distress.